(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
This research aims to identify the role that forensic accounting plays on the transparency and quality of the financial statements in trade bank of Iraq and the Gulf Commercial Bank in Babylon. This research came to address the problem that most financial institutions suffer from, which is represented by the lack of transparency and the quality of the financial statements issued in a manner. Annual also the manipulation and fraud in the financial data, which causes a big gap between that institutions and organizational stakeholders. According to the implementation of the research hypothesis and the objectives of the research, a questionnaire was prepared consisting of three axes, the first axis dealing with the demographic distribution of the sample and the second axis that included the dimensions of judicial accounting, while the third included dimensions of quality The financial statements where the Lekert five-year scale was used to measure the research variables as well as the questionnaire was distributed to the research sample of 30 employees and 30 were recovered and thus the response was 100% where some statistical methods such as the computational mean and standard deviation of the answers of the research sample were used. The coefficient of rank correlation was also used for Spearman. To measure the relationship between the research variables and use the t calculated for the meaning difference test Between the sample averages by using the spss program in analyzing the data, a set of results was reached, the most important of which was that forensic accounting is an important tool in the hands of the supervisory authorities to urge the banks of the research sample to be transparent in information and improve the quality of their financial statements. The researcher recommended the need for legal legislation defining the duties of the accountant. Judicial in both courts and financial and supervisory institutions. Key words: forensic accounting, quality of financial statements, financial reports